Estudo de caso sobre inovação na cadeia de valor na concessionária de veículos Wolkswagen Panambra Sul LTDA: uma abordagem das ameaças de disrupção e ações de inovação - Belmonte, Roberto Rivelino Fernandes (Universidade do Vale do Rio dos Sinos, 2018)
The objective of this dissertation was to develop a proposal for innovation in products and services of Panambra dealership a study of the threats of disruption and presenting a mapping of these identified threats in the value chain of the dealership. Another point developed in this research was the identification and evaluation of innovation opportunities in the Panambra value chain. The research was developed based on a case study of Panambra Car dealership and interviews with professionals from the dealership and with specialists from the automotive market. The objectives of this research are aligned with the search for alternatives and new business for the dealership Panambra, which currently faces a market in full disruption. With the car market going through difficult times, due to the arrival of carsharing applications, disruption in the car market is far from over. These are radical changes in consumer behavior in relation to the automobile.
Keywords: Automóvel; Cadeia de valor; Compartilhamento; Concessionária; Disrupção; Inovação; Estratégia; Transformação digital; Automobile; Value chain; Sharing; Dealership; Disruption; Strategy; Innovation; Digital transformation; ACCNPQ::Ciências Sociais Aplicadas::Administração